158k views
1 vote
Solve for p (1/3)(p+9)=3+2(p-6)

User Olivier Ma
by
5.5k points

2 Answers

6 votes

Answer:

36/5 or 7 1/5


Explanation:

(1/3)(p+9)=3+2(p-6)

p/3 + 9/3 = 3 + 2p - 12

p/3 + 3 = -9 + 2p

Putting the like terms together

2p - p/3 = 3 + 9

(1 2/3)p = 12

(5/3)p = 12

p = 12×3/5

= 36/5

= 7 1/5

User Nagarajan M
by
4.9k points
1 vote

Answer:


p=(36)/(5)

Explanation:

we are given


(1)/(3) (p+9)=3+2(p-6)

Since, we have to solve for p

so, we will multiply both sides by 3


3* (1)/(3) (p+9)=3* (3+2(p-6))

we can simplify it


p+9=3* 3+3* 2(p-6))


p+9=9+6(p-6))


p+9=9+6p-36


p+9-9=9+6p-36-9


p=6p-36

Subtract both sides by 6p


p-6p=6p-36-6p


-5p=-36

Divide both sides by -5

and we get


p=(36)/(5)

User Jason Wood
by
5.4k points